Homo irrationalis and climate change mitigation: Behavioral economic approaches to climate-relevant behavior change - Simon Valentin Rabaa (ResearchGate GmbH, 2023)
This dissertation explores the use of behavioral economics to advance climate change mitigation strategies. While climate change is often treated as a technical or economic problem in policy discussions, this research argues that it is ultimately also a behavioral problem. The dissertation emphasizes the role of non-rational factors in shaping human climate-relevant behavior and demonstrates how understanding these factors can help overcome barriers to effective climate policy. Three research papers provide evidence that behavioral economics can improve climate policy making by identifying new welfare implications, improving predictions of policy effects, and offering new policy tools. The first paper uses a literature-based and conceptual approach to identify and categorize status quo biases that impede individual climate-friendly behaviors, proposing measures to overcome these biases, and highlighting their potential for policy leverage. The second paper examines moral licensing rebound effects in the context of climate-related behavior, where actions perceived as morally virtuous lead to subsequent counterproductive behavior. The third paper shows how different communication framings about sufficiency behavior can increase individuals' willingness to reduce consumption.
Keywords: 330; Behavioral Economics; Climate Policy